Coincidence of Trisomy 18 and Robertsonian (13; 14) - A Jamal; S Mousavi; A Alavi (Tehran University of Medical Sciences, 2012)
This case report presents a coincidence of trisomy 18 and balanced Robertsonian translocation (13;14). Aneuploidy was suspected based on anomalies detected in ultrasound scan and confirmed with karyotype. In a 31 years-old healthy woman with a history of one miscarriage, second trimester ultrasound scan reported IUGR (<3rd percentile) with normal amniotic fluid, bilateral choroid plexus cysts, suspicious agenesis of corpus callosum and clenched hands. Amniocentesis was performed and karyotype was 46xx,der(13;14) (q10;q10),+18. Maternal karyotype was 45xx,der(13;14)(q10;q10). Pregnancy was continued due to legal limitation for termination after 20 weeks gestation. Delivery was done at 36 weeks gestation. A female newborn was borned and a physical feature was hypotonia, small mouth, prominent occiput, low-set and posteriorly rotated ears, clenched hands with overlapping fingers and rocker bottom feet. Ultrasound scan and echocardiography detected agenesis of corpus callosum and VSD, ASD, PDA and cardiomegaly. These features are typical of trisomy 18. Balanced Robertsonian translocation usually has no phenotypic expression. Genetic counseling and prenatal diagnosis for future pregnancy was recommended.